1999
DOI: 10.1038/sj.onc.1203063
|View full text |Cite
|
Sign up to set email alerts
|

The adenovirus E1A domains required for induction of DNA rereplication in G2/M arrested cells coincide with those required for apoptosis

Abstract: Induction of apoptosis by adenovirus E1A in rodent cells is stimulated by wild type (wt) p53 but completely suppressed by mutated p53. The suppression is overcome by coexpression with Id proteins (Ids). The cells expressing E1A and Ids undergo apoptosis after accumulation in S phase, suggesting that S phase events are perturbed by E1A and Ids. The E1A domains required for induction of apoptosis, analysed by transfection with expression vectors for E1A, Ids and their mutants, followed by¯ow cytometry, reside in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…It has been known for some time that the E1A proteins can induce apoptosis by both p53-dependent and p53-independent mechanisms (14,45,47,56,65,82). Induction of p53-dependent apoptosis is accompanied by accumulation of the p53 protein and requires the E1A sequences that are also necessary for transformation and mitogenesis (11,54,55,89). However, the E1B 55-kDa protein can counter these effects by several mechanisms.…”
mentioning
confidence: 99%
“…It has been known for some time that the E1A proteins can induce apoptosis by both p53-dependent and p53-independent mechanisms (14,45,47,56,65,82). Induction of p53-dependent apoptosis is accompanied by accumulation of the p53 protein and requires the E1A sequences that are also necessary for transformation and mitogenesis (11,54,55,89). However, the E1B 55-kDa protein can counter these effects by several mechanisms.…”
mentioning
confidence: 99%
“…Moreover, E1a protein has been shown to provoke endoreduplication of DNA and drive cells to apoptosis from cells in G2 cell cycle phase. 28 The TK system has also been studied with replicative-conditional adenovirus trying to enhance the effects of both antitumoral strategies. In fact, Wildner 30 using an E3 -deleted adenoviral vector containing the HSVTK -suicide gene driven by the endogenous E3 promoter.…”
Section: Discussionmentioning
confidence: 99%
“…10 More importantly, Id-1 was found to bind to the N-terminal region of the adenovirus protein E1A and augment its effect on induction of cellular apoptosis. 11 These findings suggested that Id-1 might be a common cellular target of viral proteins.…”
Section: Introductionmentioning
confidence: 97%